Suicidal Ideation in Adolescents: A Literature Review of Risk Factors and Prevention Efforts - Kurnia Sari, Dhita (Universitas STRADA Indonesia, 2025)
Suicidal ideation in adolescents is a serious mental health problem that continues to increase in various countries. This article presents a literature review of the main risk factors that contribute to the emergence of suicidal ideation in adolescents, such as depression, academic pressure, domestic violence, social media use, and stigma towards mental health issues. In addition, this article discusses effective prevention strategies, including school-based interventions, family involvement, and mental health services. The research method used is a literature review by searching for scientific articles from databases such as PubMed, Scopus, and Google Scholar, with a publication range between 2013 and 2023. The reviewed articles were selected based on their relevance to the topic and methodological quality. This review shows the need for a multidisciplinary and collaborative approach to address this problem comprehensively. Keywords: suicidal ideation, adolescents, mental health, risk factors, prevention